2012
DOI: 10.1002/jcc.23163
|View full text |Cite
|
Sign up to set email alerts
|

Rate coefficients of the CF3CHFCF3 + H → CF3CFCF3 + H2 reaction at different temperatures calculated by transition state theory with ab initio and DFT reaction paths

Abstract: The minimum energy path (MEP) of the reaction, CF3CHFCF3 + H → transition state (TS) → CF3CFCF3 + H2, has been computed at different ab initio levels and with density functional theory (DFT) using different functionals. The computed B3LYP/6‐31++G**, BH&HLYP/cc‐pVDZ, BMK/6‐31++G**, M05/6‐31+G**, M05‐2X/6‐31+G**, UMP2/6‐31++G**, PUMP2/6‐31++G**//UMP2/6‐31++G**, RCCSD(T)/aug‐cc‐pVDZ//UMP2/6‐31++G**, RCCSD(T)/aug‐cc‐pVTZ(spd,sp)//UMP2//6‐31++G**, RCCSD(T)/CBS//M05/6‐31+G**, and RCCSD(T)/CBS//UMP2/6‐31++G** MEPs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Consequently, it is difficult to benchmark lower levels in the present study, as has been pointed out before [36,38]. Also, similar to our recent findings [36], employing different lower levels with the same higher level improved relative energies gives spreads in computed rate coefficients of at least an order of magnitude, which may be considered generally as uncertainties associated with any lower level employed.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Consequently, it is difficult to benchmark lower levels in the present study, as has been pointed out before [36,38]. Also, similar to our recent findings [36], employing different lower levels with the same higher level improved relative energies gives spreads in computed rate coefficients of at least an order of magnitude, which may be considered generally as uncertainties associated with any lower level employed.…”
Section: Discussionsupporting
confidence: 66%
“…Also, similar to our recent findings [36], employing different lower levels with the same higher level improved relative energies gives spreads in computed rate coefficients of at least an order of magnitude, which may be considered generally as uncertainties associated with any lower level employed. In addition, in the present study with more extensive investigations at dual levels than in our previous works [36,37,38], basis size effects at higher levels were found to be related to geometry effects from lower levels (i.e. different basis size effects at different geometries).…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Moreover, log 10 k versus 1000/T plots, which are used commonly in experimental rate studies, [63] are also reported. [64] We examined the maxima of both classical potential energy, V MEP , and the ground-state adiabatic potential energy, V a G , which had no shifting. [64] We examined the maxima of both classical potential energy, V MEP , and the ground-state adiabatic potential energy, V a G , which had no shifting.…”
Section: Reaction Coefficients and Dynamicsmentioning
confidence: 99%